2003
DOI: 10.1097/00004872-200310000-00002
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein and interleukin-6 in vascular disease

Abstract: Recent advances in basic science have shown that atherosclerosis should be considered as a chronic inflammatory process, and that a pivotal role of inflammation is evident from initiation through progression and complication of atherosclerosis. In the past few years many studies have examined the potential for biochemical markers of inflammation to act as predictors of coronary heart disease (CHD) risk in a variety of clinical settings. Several large, prospective epidemiological studies have shown consistently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
112
2
13

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(128 citation statements)
references
References 210 publications
(197 reference statements)
1
112
2
13
Order By: Relevance
“…1,9 Inflammatory markers such as CRP and IL-6 not only participate in lesion formation but also in the plaque architecture that favours rupture. 7 A number of studies have shown that increased blood pressure has an important influence on elevated levels of circulating IL-6 4 and hs-CRP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,9 Inflammatory markers such as CRP and IL-6 not only participate in lesion formation but also in the plaque architecture that favours rupture. 7 A number of studies have shown that increased blood pressure has an important influence on elevated levels of circulating IL-6 4 and hs-CRP.…”
Section: Discussionmentioning
confidence: 99%
“…3 Indeed, hypertensive patients who were free from any other important medical conditions were reported to have high circulating levels of proinflammatory cytokines such as tumor necrosis factor-a (TNF-a), interleukin-6 (IL-6), 4 and C-reactive protein (CRP). 5,6 These cytokines may cause inflammation of the endothelium, 7,8 which can cause further damage to the endothelium 9 and the elevation of blood pressure. One of the most useful factors for estimating the inflammatory response and the risk for vascular events is high sensitive CRP (hs-CRP).…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30] Thus, some authors proposed IL-6 as a useful prognostic marker of CVD outcome [31][32][33][34][35][36][37] and suggested a central role for IL-6 in the pathogenesis of CHD. [38][39][40] However, the estimated heritability for IL-6 ranged between 0.17 and 0.57 in the literature 16,41,42 and previous studies concerning the heritability of CRP and IL-6 have to be interpreted carefully (Table 1). The design and exact analysis differed (twin to general family studies, VogelMotulsky heritability to other variance composition methods) and the correction for possible confounders varied greatly between the studies (different confounders considered, different methods).…”
mentioning
confidence: 97%
“…É produzida e liberada pelos hepatócitos sendo a IL-6 a maior indutora de sua síntese, enquanto um papel menor está atribuído a outras citocinas como a IL-1 e o TNF-α (23). Dentre as propriedades pró-inflamatórias da CRP estão a sua capacidade de reconhecer e promover a fagocitose dos micro-organismos e das células agredidas no processo inflamatório; promover a ativação dos monócitos/macrófagos por aumentar a síntese e secreção de IL-1 e TNF-α e induzir a expressão de moléculas de adesão e secreção de IL-6 pelas células endoteliais (23).…”
Section: • Proteína C-reativa Como Marcador Biológico Inflamatóriounclassified